Argentina’s Constituent Genocide: Challenging the Hegemonic National Narrative and Laying the Foundation for Reparations to Indigenous Peoples - Lenton, Diana Isabel (2012)
For more than a century, there has been little discussion of the Argentinean genocide perpetrated against indigenous peoples. As a result, presently a majority of Argentines perceive their identity and society as the outcome of a “European melting pot” process, not the result of genocide. In this view, sixteenth century European colonization of a territory imagined as a “desert” and the expansion of the nation-state by the late 19th Century are the historical processes that account for this melting pot. This article deals with the events and effects of the last period of territorial annexation and subjugation of the indigenous peoples perpetrated by the Argentinean national armed forces between 1876 and 1917, focusing on the state’s genocidal policies and the support from civil society. Paradoxically, these actions as a whole have been named in the hegemonic national history of Argentina’s “Campaigns to the Desert.”1 This formulation and the national narratives it names minimize or deny completely the existence of indigenous peoples in the areas annexed. The aim of this paper is to examine the construction and effects of the genocide of the indigenous population as an event excluded from the national narrative and literally “unthinkable” by average Argentines. In the present, different groups –such as indigenous peoples’ organizations, academic researchers, and alternative media– have started to make visible this genocidal process that is constitutive of the Argentinean nation state. The exposure of the facts of history has generated a growing debate on the historical processes. In this context, a series of specific but related processes of violence and conquest can be identified and described. We term these “genocide-prints,” through which we will consider not only the genocide but also the current debates on reparations to indigenous peoples.